Irrigation suitability of North Bengal Sugar Mills effluent and its impact on soil properties (Journal of the Bangladesh Agricultural University, 2012)
The suitability of effluent water (hereafter called wastewater) from North Bengal Sugar Mill (NBSM) for irrigation and its impact on soil properties were evaluated. The quality parameters of wastewater from three different locations of the drainage canal and one freshwater sample from a hand tubewell of the NBSM complex were determined. The major physico-chemical and hydraulic properties of the wastewater affected and unaffected soils from West Baiddanathpur village (hereafter referred to as site 1) and East Baiddanathpur village (hereafter referred to as site 2) were determined. The electrical conductivity (EC) and pH of the wastewater were 0.78?1.05 dS m?1 and 6.6?6.95, respectively. The wastewater was richer than the freshwater in terms of nitrogen (15.8?24.7 mg l?1) and phosphorous (5.2?6.0 mg l?1) contents. The iron (0.37?0.49 mg l?1), manganese (0.3?0.9 mg l?1) and boron (0.43?0.51 mg l?1) concentrations were higher in the wastewater than in the freshwater. The biological oxygen demand (BOD) and chemical oxygen demand (COD) of the wastewater was 183?309 mg l?1 and 196?685 mg l?1, respectively. All these chemical constituents decreased with the flow path of the wastewater. Temperature of the wastewater at the head end of the disposal canal was 39.5oC that decreased to the ambient temperature at the downstream. The BOD, COD and temperature of the wastewater exceeded the threshold values for irrigation and, therefore, this water would not be suitable for irrigation without treatment. The wastewater elevated the EC and reduced the pH of soil. It however improved soil fertility by improving the phosphorous, potassium, sulphur and organic matter contents. It also elevated the porosity and reduced the bulk density of soil. The soil-water content at field capacity and the saturated hydraulic conductivity increased due to the effect of wastewater.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11042   J. Bangladesh Agril. Univ. 9(2): 283290, 2011